Multi‐Instrumental Observations of Nonunderdense Meteor Trails. Issue 7 (27th July 2018) - Kozlovsky, A.; Shalimov, S.; Kero, J.; Raita, T.; Lester, M.
Abstract: Using data from the Sodankylä Geophysical Observatory (67°22′N, 26°38′E, Finland) meteor camera from the whole year 2015, we identified and investigated 28 optical meteors with accompanying ionization trails unambiguously detected by the Sodankylä Geophysical Observatory ionosonde, which sounded the ionosphere once per minute with frequency rising from 0.5 to 16 MHz. These ionosonde reflections were obtained from heights around 90 km. The electron line densities of the trails were found to be between 10 14 and 10 16 m −1, which characterize the trails as nonunderdense (i.e., transitional and overdense). The ionosonde reflections were observed for a few minutes, with decreasing maximal frequency of the return. During the first 250 s, for the trails with initial line density about (2–3) · 10 15 m −1 the return frequency decreased with time corresponding to the diffusional expansion of cylindrical meteor trails, that is, f ∝ t − γ, where the exponent γ = 0.5, whereas less dense trails decayed slower ( γ ≈ 0.2) and more dense trails decayed faster ( γ ≈ 1). In many cases the meteor events were accompanied by nonspecular long‐lived detections using a colocated all‐sky interferometric meteor radar with operating frequency 36.9 MHz. As a rule the meteor radar echo durations were longer than expected from diffusional expansion of cylindrical meteor trails and their amplitudes were highly variable. We suggest that the slower frequency decrease of the ionosonde echoes and the nonspecular long‐lived meteor radar echoes might be associated with the presence of meteoric dust. Key Points: Optical, ionosonde, and meteor radar observations of non‐underdense (transitional and overdense) meteor trails were made at high latitude During the first 4 min the decay rate of ionosonde echo depends on initial electron line density of trails (empirical dependence obtained) Meteor events were accompanied by nonspecular long‐lived detections using a colocated meteor radar with operating frequency 36.9 MHz